Comparison of non-invasive scores predictive of development of metabolic dysfunction associated liver disease in patients of type 2 diabetes mellitus and evaluation of additive effect of smoking in these patients - Singla, Heena (International Journal of Research in Medical Sciences, 2024)
Background: Metabolic dysfunction associated liver disease (MASLD) has been found to be at alarming increase in Indian population. Prevalence of metabolic syndrome including Type 2 Diabetes Mellitus is also increasing which may be attributed to certain lifestyle changes. In the present study, we compared the likelihood of liver fibrosis by measurement of non-invasive scores among Type 2 diabetics and smokers, Type 2 diabetics but non-smokers and healthy controls. Our study will provide useful insights to evaluate the association between Type 2 diabetes, smoking and development of MASLD. Methods: The study was done at a tertiary care hospital. Participants were divided into 3 groups (each of 40 participants) which included those with type 2 diabetes mellitus and smokers, those with type 2 diabetes mellitus but non-smokers and healthy controls. Parameters included in the database were age, sex, body mass index, history of diabetes, history of hypertension, any medication, tobacco use and alcohol consumption. Venous blood samples were taken in the morning after a 12-h overnight fasting and investigations were done. Results were recorded. Results: FIB-4 score and AST/ALT ratio was significantly higher in diabetics and smoker patients, in comparison to diabetics but non-smokers and healthy controls. Conclusions: Smoking and underlying type 2 diabetes mellitus have a synergistic effect on the severity of fibrosis, as compared to nonsmokers with type 2 diabetes mellitus. Hence smoking cessation, in addition to glycemic control with regular medication, may be beneficial in reducing the severity of MASLD among patients with type 2 diabetes mellitus.